Harmonization of Islamic Economics With Artificial Intelligence: Towards an Ethical and Innovative Economic Paradigm - Ishak, Muhammad Nur; Mohamed, Adjila (LP2M IAIN Palopo, 2023)
The linkage between Islamic economics and artificial intelligence (AI) is the basis of research to explore the possibility of integration of these two entities in creating an ethical and innovative economic paradigm. This article explores the potential and challenges of achieving harmonization between Islamic economic principles underlying justice and sustainability with the sophistication of AI technology. The main focus of the research is on how artificial intelligence applications, such as machine learning and big data analysis, can be applied to improve operational efficiency and decision-making in accordance with Islamic values. The article also discusses the ethical implications of the use of artificial intelligence in the context of Islamic economics, highlighting the importance of maintaining a balance between technological innovation and Islamic moral principles. Economic empowerment, equitable distribution of wealth, and prudent risk management are key focuses in evaluating AI's contribution to the Islamic economic ecosystem. In an effort to achieve a harmonious economic paradigm, this article proposes a proactive approach to mitigate risks and ensure that the use of AI technology in the context of Islamic economics is in accordance with the ethical framework and Islamic values. The results of research on the harmonization of Islamic economics with artificial intelligence yield significant insights into the potential and impact of this integration on economic paradigms. One of the key findings is that this harmonization opens the door to innovative solutions to address a range of contemporary economic challenges.